2013
DOI: 10.1159/000350231
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Spectral Domain Optical Coherence Tomography Analysis of Subretinal Deposits in Patients with Acute Central Serous Retinopathy

Abstract: Purpose: To perform qualitative and quantitative analyses of subretinal protein deposits (PDs), seen in acute central serous retinopathy (CSR) patients, using high-resolution spectral domain optical coherence tomography (SD-OCT), in order to investigate whether the present PDs have any significant impact on best corrected visual acuity (BCVA). Methods: Patients diagnosed with acute CSR were included. Using SD-OCT, the following distances/heights were measured: central total retinal thickness, central neurosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
7
1
1
Order By: Relevance
“…29 Their presence were found to be correlated not only to disease duration, but also to poorer final visual acuity. 30,31 Interestingly, despite the fact that both biomarkers found in our study population were earlier attenuated to the chronic form of CSCR, no significant difference was found in disease duration or phenotype (recurrent or continuous, mono or multifocal) between the good and poor responder groups. One explanation for these results could be that in recurrent and chronic CSCR the duration of neurosensory detachment is often doubtful.…”
Section: Sacconi Et Al Reported Possible Biomarkers On Icg-angiograpcontrasting
confidence: 54%
“…29 Their presence were found to be correlated not only to disease duration, but also to poorer final visual acuity. 30,31 Interestingly, despite the fact that both biomarkers found in our study population were earlier attenuated to the chronic form of CSCR, no significant difference was found in disease duration or phenotype (recurrent or continuous, mono or multifocal) between the good and poor responder groups. One explanation for these results could be that in recurrent and chronic CSCR the duration of neurosensory detachment is often doubtful.…”
Section: Sacconi Et Al Reported Possible Biomarkers On Icg-angiograpcontrasting
confidence: 54%
“…Intraretinal hyper-reflective dots at the level of outer plexiform layer (OPL), outer nuclear layer (ONL), ELM, IS/OS band have been reported in 21–100% of all CSCR forms 17. Hyper-reflective dots when present in intraretinal or subretinal layer have been correlated with lower final BCVA 3,16,18,19. Also, they were found to be the only OCT parameter associated with the non-resolution of SRF 20…”
Section: Discussionmentioning
confidence: 99%
“…These alterations in retinal morphology may also be a factor in the poorer visual acuity outcomes in male subjects. Indeed, subretinal deposits themselves in CSC have been correlated with poorer visual function [12]. Interestingly, female patients appeared to show a reduction in subretinal deposits at follow-up compared with the male subjects, suggesting perhaps that these factors may be of use in the assessment of disease chronicity.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative and qualitative analysis of optical coherence tomography (OCT)-derived images has revealed that there are a number of structural changes in CSC in addition to neurosensory detachment (NSD). Whilst subfoveal choroidal thickness (CT) has been shown to be higher in eyes with CSC, various morphological features have also been investigated including pigment epithelial detachment (PED), subretinal deposition and hyperreflective foci [9][10][11][12][13]. Variation in visual acuity outcomes has been suggested to be partly due to alterations in these structural features.…”
Section: Introductionmentioning
confidence: 99%